TRANSFORMASI PEDAGOGIS MELALUI DEEP LEARNING DALAM KURIKULUM MERDEKA: STUDI LITERATUR SISTEMATIS - Syaifulloh, Rizal Bagus (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
Global developments in education have prompted a paradigm shift from knowledge transmission–oriented learning toward deep, reflective, and contextual conceptual understanding. In Indonesia, the Deep Learning (DL) approach has been introduced as a pedagogical strategy to strengthen the implementation of the Merdeka Curriculum by fostering 21st-century competencies articulated in the 6Cs framework. However, numerous studies indicate a gap between the ideal conception of DL and its classroom implementation, where it is often narrowly interpreted as the use of digital technology or specific instructional models. This study aims to examine teachers’ understanding, implementation patterns, and systemic challenges related to Deep Learning in Indonesia through a Systematic Literature Review (SLR) guided by the PRISMA protocol. The findings reveal that while teachers generally demonstrate positive perceptions of DL, comprehensive instructional understanding remains limited. Learning practices that integrate meaningful, mindful, and joyful principles have been shown to enhance student engagement and reasoning skills, particularly when supported by strong pedagogical beliefs and a collaborative school culture. Major barriers include limited professional development, infrastructure disparities, and administrative workloads that constrain pedagogical innovation. This study concludes that Deep Learning holds substantial potential as a vehicle for pedagogical transformation and educational equity; however, its sustainability requires systemic change through the strengthening of teacher capacity and the cultivation of a holistic learning culture. ABSTRAKPerkembangan pendidikan global mendorong terjadinya pergeseran paradigma pembelajaran dari sekadar transfer pengetahuan menuju pemahaman konseptual yang mendalam, reflektif, dan kontekstual. Di Indonesia, pendekatan Deep Learning (DL) diperkenalkan sebagai strategi pedagogis untuk memperkuat implementasi Kurikulum Merdeka melalui pengembangan kompetensi abad ke-21 yang dirumuskan dalam kerangka 6Cs. Namun, berbagai studi menunjukkan adanya kesenjangan antara konsep ideal dan praktik di lapangan, di mana DL kerap dipersepsikan sebatas penggunaan teknologi atau model pembelajaran tertentu. Penelitian ini bertujuan untuk menganalisis pemahaman guru, bentuk implementasi, serta hambatan sistemik dalam penerapan Deep Learning di Indonesia melalui metode Systematic Literature Review (SLR) dengan mengacu pada protokol PRISMA. Hasil kajian menunjukkan bahwa meskipun guru umumnya memiliki persepsi positif terhadap DL, tingkat pemahaman instruksional yang komprehensif masih terbatas. Implementasi yang mengintegrasikan prinsip meaningful, mindful, dan joyful learning terbukti meningkatkan keterlibatan serta kemampuan bernalar peserta didik, terutama ketika didukung oleh keyakinan pedagogis guru dan budaya sekolah yang kolaboratif. Hambatan utama meliputi keterbatasan pelatihan, ketimpangan infrastruktur, serta beban administratif yang menghambat inovasi pembelajaran. Penelitian ini menegaskan bahwa Deep Learning berpotensi menjadi instrumen transformasi pedagogis dan keadilan pendidikan, namun keberlanjutannya menuntut perubahan sistemik melalui penguatan kapasitas guru dan pengembangan budaya belajar secara menyeluruh.